Investigación sobre los criterios tributarios para la formalización de empresas culturales sin ánimo de lucro en Medellín (2017)
The present research is oriented to demonstrate different tributaries elements that cultural organizations in “Comuna 6: Doce de Octubre Medellín” have to take into account when they are creating artistic and cultural events. Those organizations have the capacity to organize permanent artistic and cultural events within the same territory, but in some way they are unaware of the applicability of the law, as well as the interpretation of the norm and the legalization of the same. Thus, this work contains an analysis of laws, decrees and tax regulations at a general level, among other aspects of a legal nature, which must be taken into account in order to avoid making a mistake in the execution of projects. This project is intended to seek and present a clear and coherent way to understand the current regulations in the elaboration of artistic and cultural projects necessary for the different public tenders that “Alcaldía de Medellín” makes available to the community in general, as well as to know deeply the benefits that can be Obtain, or even reductions in the taxes payment, following this statement this research is aim to develop more assertive ways to contribute to the social development of this communities.